Uji efektivitas ekstrak etanol daun senggani (Melastoma malabathricum L.) sebagai antihipertensi pada mencit putih jantan (Mus musculus) - Lilik Septiana; Rida Evalina Tarigan; Muhammad Andry; Vannissa Andriani Irawan; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Senggani leaves have secondary metabolites that can inhibit the release of aldosterone so that more water is removed from the body and blood pressure will drop. Objectives; The purpose of this study was to determine the effectiveness of the ethanol extract of senggani leaves (Melastoma malabathricum L.) on reducing blood pressure of male white mice (Mus musculus). Method; this research is experimental which includes sampling, sample processing, extract making, simplicia characteristics, preparation of test materials, treatment of test animals and data analysis. The samples used were senggani leaves (Melastoma malabathircum L.). The test animals used were 15 male white mice then divided into 5 groups. Measurement of blood pressure using a blood pressure analyzer with the tail cuff method. The measurement data were then analyzed using a paired t-test with a significance limit of 0.05. Result; showed that the ethanol extract of senggani leaves had antihypertensive effectiveness with the lowest systolic blood pressure measurement results after treatment at EEDS 150 mg/kgBW which was 86.66 mmHg and diastolic blood pressure obtained the lowest after treatment at EEDS 150 mg/KgBW, which was 59 mmHg. . The results of the statistical paired t-test showed that there was an effect of giving the test material EEDS 50 mg/kgBW, EEDS 100 mg/kgBW, EEDS 150 mg/kgBW test for 14 days with p-value <0.05. On diastolic blood pressure, the effect of treatment with the test material on blood pressure was significant at EEDS 150 mg/kgBW with p-value = 0.001. Conclusion; this study was that the administration of the ethanol extract of the leaves of senggani (Melastoma malabathricum L.) could reduce the blood pressure of experimental male mice (Mus musculus). The ethanol extract of senggani leaves (Melastoma malabathricum L.) was effective in lowering blood pressure at a dose of 150 mg.